Ligand‐Regulated Regiodivergent Hydrosilylation of Isoprene under Iron Catalysis. (20th August 2020) - Kuai, Chang‐Sheng; Ji, Ding‐Wei; Zhao, Chao‐Yang; Liu, Heng; Hu, Yan‐Cheng; Chen, Qing‐An
Abstract: A method for the regiodivergent and stereoselective hydrosilylation of the basic industrial feedstock isoprene with unactivated silanes has been developed using earth‐abundant iron catalysts. The manipulation of regioselectivity relies on fine modification of the coordination geometry of the iron center. While a bidentate pyridine imine ligand promoted the formation of allylic silanes through 4, 1‐addition, selectivity for the 3, 4‐adduct homoallylic silanes was observed with a tridentate nitrogen ligand. Experimental studies and analysis were carried out to elucidate the reaction mechanism and the factors enabling manipulation of the regioselectivity. This study contributes to the art of regioselectivity control in alkene hydrofunctionalization. Abstract : A ligand‐regulated regiodivergent and stereoselective hydrosilylation of terpenes has been developed using earth‐abundant iron catalysts. Various silanes and terpenes were transformed with excellent selectivity into the corresponding allylic silanes and homoallylic silanes through 4, 1‐ and 3, 4‐addition, respectively.